Identifying Immigrating Sogatella furcifera (Hemiptera: Delphacidae) Using Field Cages: A Case Study in the Yuanjiang (Red River) Valley of Yunnan, China. Issue 1 (1st February 2019) - Hu, Shao-Ji; Dong, Li-Min; Wang, Wen-Xin; Chen, Sui-Yun; Ye, Hui
Abstract: The white-backed planthopper, Sogatella furcifera (Horváth), is a devastating migratory rice pest in South China; lack of effective methods to identify immigrating populations is the main cause of difficulties in outbreak forecasting, active prevention, and control. The current study set up field cages (2 × 2 × 3 m each, US-80 standard nylon mesh) in both early- and mid-season paddies in Yuanjiang (Red River) Valley in Yunnan, China, in 2012 and 2014. The immigrating population was successfully separated from the local population of S. furcifera and identified using statistical comparisons. The findings showed that densities of macropterous adults outside the cages were all significantly higher than those inside the cages on both early- and mid-season rice in both years, whereas the densities of young nymphs and old nymphs showed no significant differences. This indicated that immigrations were occurring, the earliest of which occurred on early-season rice in early May and reached its peak in mid-late May before a rapid collapse in both years. In contrast, the immigration on mid-season rice showed a continuous decline or fluctuation throughout the entire period. Analyses demonstrated that the migration process of S. furcifera in the Yuanjiang Valley features continuous immigration from the adjacent southern parts of Yunnan, which may represent most migration events in Yunnan during the outbreak period of a year. The findings of this case study could benefit our understanding of planthopper migration and outbreaks in other parts of China, especially where the outbreak pattern is very different from Yunnan.